Kemampuan Pemecahan Masalah Matematika Siswa pada Pembelajaran Matematika Menggunakan Strategi Abduktif-Deduktif di SMA Negeri 1 Indralaya Utara - Ariani, Suci; Hartono, Yusuf; Hiltrimartin, Cecil (Universitas Hamzanwadi, 2017)
This research is aimed to describe studentsâ problem solving skill in mathematics learning using abductive-deductive strategy. This research is descriptive research with 30 students of X.3 class at SMAN 1 Indralaya Utara as the subject. Learning process accords to characteristic and steps of abductive-deductive strategy in mathematics learning. The technique for collecting data is a test which includes of three problems. According to the results of research, it is obtained that representation of studentsâ problem solving skill in mathematics learning using abductive-deductive strategy on X.3 class at SMAN 1 Indralaya Utara is medium with these details: 2 students have very high problem solving skill or the percentage is 6,67%, 12 students have high problem solving skill or the percentage is 40%, 11 students have medium problem solving skill or the percentage 36,67%, and 5 students have low problem solving skill or the percentage is 16,67% and 0% or nothing who have problem solving skill with category very low. Furthermore, the understanding problem indicator has the highest percentage at 89,63%. Indicator of making a plan has the percentage at 63,7%, indicator of carrying out the plan has the percentage at 45,56%, and the looking back indicator has the lowest percentage at 16,11%.